Novel immunohistochemical markers for the differentiation of lobular and ductal invasive breast carcinomas - Turashvili, Gulisa; Bouchal, Jan; Ehrmann, Jiri; Fridman, Eduard; Skarda, Jozef; Kolar, Zdenek (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
AIMS: Invasive ductal and lobular carcinomas are the most common histological types of breast cancer. The loss of E-cadherin expression has been suggested to be the most reliable marker for invasive lobular carcinoma. The aim of our study was to identify the diagnostic usefulness of novel markers in the differentiation of these tumor types. METHODS: We examined tissue microarrays (TMA) which were constructed from surgical specimens of 119 breast cancer patients. TMA consisted of 80 ductal carcinomas, 29 lobular carcinomas and special type cancers. TMA sections were stained using standard immunohistochemical methods. Monoclonal mouse antibodies against E-cadherin, cytokeratin 5/6 and 17, and polyclonal mouse antibodies against EMP1, DDR1, PRKCI and DVL1 were used. RESULTS: E-cadherin was absent in 93.3% of lobular tumors compared with only 15 % of ductal tumors (p<0.0001). EMP1 and DVL1 were overexpressed in lobular tumors (93.1% and 96.5%, respectively), whereas PRKCI and DDR1 were positive in ductal cancers (90% and 96.2%, respectively). Reduced expression or absence of both cytokeratins 5/6 and 17 was found in both tumor tissues in comparison to normal terminal duct lobular units (p<0.0001). CONCLUSIONS: Apart from the well-established marker, E-cadherin, proteins examined on TMA slides by immunohistochemistry (EMP1, DVL1, DDR1, PRKCI) may represent novel tissue markers helpful in the differentiation of ductal and lobular breast cancers. Further studies with larger sets of patients are desirable, to verify the complete immunohistochemical profiles of various histological types of breast cancer and determine the prognostic and predictive significance of novel markers.
Keywords: diferenciální diagnóza; Carcinoma, Ductal, Breast; Breast Neoplasms; imunohistochemie; Tissue Array Analysis; Carcinoma, Lobular; čipová analýza tkání; Adult; Biomarkers, Tumor; lobulární karcinom; duktální karcinom prsu; Immunohistochemistry; ženské pohlaví; nádorové biomarkery; Humans; Diagnosis, Differential; nádory prsu; dospělí; Female; lidé